Buyang Huanwu decoction affects gut microbiota and lipid metabolism in a ZDF rat model of co-morbid type 2 diabetes mellitus and obesity: An integrated metabolomics analysis - Liu, Mei; Zhao, Qinmian; Liu, Jiayan; Huang, Aijing; Xia, XinHua (Frontiers in Chemistry, 2022)
Type 2 diabetes mellitus (T2DM) is a chronic disease associated with many severe complications such as blindness, amputation, renal failure, and cardiovascular disease. Currently, the prevention and treatment of T2DM is a major global challenge as the number of aging and obese people is increasing. Traditional Chinese medicine offers the advantages of multi-target holistic and individual treatment for obesity and type 2 diabetes. However, most of the TCMs for T2DM are not scientifically evaluated. Here, Buyang Huanwu decoction (BYHWD), a widely used TCM formula, was used to explore scientific pharmacological activity against T2DM in rat models. First, BYHWD exhibited excellent inhibitory actions against body fat accumulation and increased blood triglyceride levels, and a high-fat diet (HFD) induced blood glucose elevation in diabetic rats. Moreover, 16S rDNA sequencing of fecal samples identified the distinct changes in the community composition of gut flora following BYHWD treatment, displayed as significantly increased Bacteroidetes and dramatically decreased Firmicutes at the phyla level, and the remarkable increase in the abundance of Lactobacillus and Blautia. Additionally, lipid metabolomics based on liquid chromatography–mass spectrometry revealed a significant shift of lipid metabolites in the liver after BYHWD treatment. Notably, these differential lipid metabolites were particularly involved in biological processes such as cholesterol metabolism, linoleic acid metabolism, glycerolipid metabolism, glycerophospholipid metabolism, insulin resistance, arachidonic acid metabolism, and alpha-linoleic acid metabolism. Importantly, Spearman correlation analyses suggested an association between disturbed gut microbiota and altered lipid metabolites. Moreover, they were also closely associated with the bioactivities of BYHWD to reduce the blood lipid and blood glucose levels. Collectively, these results suggest that BYHWD could meliorate gut microbiota dysbiosis and lipid metabolite alterations induced by the HFD in diabetic rats. These results not only provide a novel perspective on understanding the mechanisms underlying BYHWD bioactivity against T2DM but also suggest the use of advanced systems biology methods to reveal some unknown scientific laws in TCM theories.